Proceedings of the 5th International Conference on Predictor Models in Software Engineering 2009
DOI: 10.1145/1540438.1540448
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the evaluation of defect prediction models

Abstract: Defect Prediction Models aim at identifying error-prone parts of a software system as early as possible. Many such models have been proposed, their evaluation, however, is still an open question, as recent publications show.An important aspect often ignored during evaluation is the effort reduction gained by using such models. Models are usually evaluated per module by performance measures used in information retrieval, such as recall, precision, or the area under the ROC curve (AUC). These measures assume tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
105
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 30 publications
3
105
0
Order By: Relevance
“…Traditional performance metrics used in most previous work are precision, recall, f-measure, AUC [23], error sum, median error, error variance, and correlation [3]. Mende and Koschke [6], Arisholm et al [25], and Rahman et al [26] suggested that traditional performance metrics are not wellsuited for evaluating defect prediction approaches in a practical scenario. Indeed, for traditional metrics, all defect prone software artifacts have the same priority while software engineers would benefit from identifying those software components containing more defects earlier.…”
Section: Background and Problem Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Traditional performance metrics used in most previous work are precision, recall, f-measure, AUC [23], error sum, median error, error variance, and correlation [3]. Mende and Koschke [6], Arisholm et al [25], and Rahman et al [26] suggested that traditional performance metrics are not wellsuited for evaluating defect prediction approaches in a practical scenario. Indeed, for traditional metrics, all defect prone software artifacts have the same priority while software engineers would benefit from identifying those software components containing more defects earlier.…”
Section: Background and Problem Descriptionmentioning
confidence: 99%
“…Indeed, for traditional metrics, all defect prone software artifacts have the same priority while software engineers would benefit from identifying those software components containing more defects earlier. As pointed out by Mende and Koschke [6] and D'Ambros et al [3] the scenario that is more useful in practice is to rank the classes by the predicted number of defects they will exhibit. In the context of defect prediction, prediction models assign a defect probability to all classes, according to which they can be ranked.…”
Section: Background and Problem Descriptionmentioning
confidence: 99%
See 3 more Smart Citations